The Effect of Intraoperative Systemic Lidocaine on Postoperative Persistent Pain Using Initiative on Methods, Measurement, and Pain Assessment in Clinical Trials Criteria Assessment Following Breast Cancer Surgery: A Randomized, Double‐Blind, Placebo‐Controlled Trial - Kendall, Mark C.; McCarthy, Robert J.; Panaro, Steve; Goodwin, Emily; Bialek, Jane M.; Nader, Antoun; De Oliveira, Gildasio S. (Pain practice, 2018)
Objective To compare the incidence in postsurgical persistent pain following breast cancer surgery in women receiving intravenous lidocaine compared to saline using validated pain instruments in accordance with the Initiative on Methods, Measurement, and Pain Assessment in Clinical Trials (IMMPACT) recommendations. Methods The study was a randomized, double‐blinded, placebo‐controlled, clinical trial. Subjects were randomized into Group 1 (1.5 mg/kg bolus of intravenous lidocaine followed by a 2 mg/kg/hour infusion) or Group 2 (normal saline at the same bolus and infusion rate). Patients were evaluated at 3 and 6 months for the presence of chronic persistent postsurgical pain. Results One hundred forty‐eight patients were included in the study analysis. There were no differences in quality of recovery, pain burden, or opioid consumption between groups at 24 hours. Pain (yes/no) at 6 months attributed to surgery was reported in 29% of Group 2 vs. 13% of Group 1 patients (P = 0.04); however, only 3 subjects (5%) in Group 1 and 2 subjects (3%) in Group 2 met IMMPACT criteria for persistent postoperative pain (P = 0.99). Discussion Perioperative infusion of lidocaine has been reported to decrease the incidence of postsurgical pain at 3 and 6 months following mastectomy using dichotomous (yes/no) scoring. Although intravenous lidocaine reduced the reported incidence of pain at rest at 6 months, pain with activity, pain qualities, and the physical or emotional impact of the pain were unaffected. Future studies evaluating postsurgical persistent pain should adhere to the IMMPACT recommendations in order to more accurately describe the effect of an intervention on persistent pain.